The role of necroptosis, an alternative form of cell death, in cancer therapy. Issue 7 (July 2013) - Yu, Xinfang; Deng, Qipan; Bode, Ann M; Dong, Zigang; Cao, Ya
Programmed cell death plays an important role in animal development, tissue homeostasis and eliminating harmful or virally infected cells. Necroptosis, a novel form of programmed cell death, is caspase independent but RIPK and RIPK3 dependent. Moreover, it is suggested that necroptosis can be specifically inhibited by small molecular inhibitors such as necrostatin-1. Its signaling pathways have something in common with apoptosis, although the molecular mechanisms of necroptosis need to be further elucidated. Previous evidences suggest that necroptosis has significant effects in regulating various physiological processes and disease, such as ischemic brain injury, immune system disorders and cancer. In this review, the molecular mechanism of necroptosis is described and how it could be manipulated in the treatment of cancer is summarized.